2012
DOI: 10.1159/000342377
|View full text |Cite
|
Sign up to set email alerts
|

Increased Time Exposure to Tenofovir Is Associated with a Greater Decrease in Estimated Glomerular Filtration Rate in HIV Patients with Kidney Function of Less than 60 ml/min/1.73 m<sup>2</sup>

Abstract: Tenofovir (TDF), atazanovir (ATAZ) and indinavir (IND) have been reported as possible risk factors for incident chronic kidney disease (CKD) in HIV-infected patients. We investigated the relationship between the duration of antiretroviral exposure and estimated glomerular filtration rate (eGFR) evolution in CKD patients. In a cohort of 1,750 HIV-infected patients, we identified 121 CKD patients with a mean follow-up of 44 ± 35 months. The relationship between mean eGFR at baseline, eGFR slope and time exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 93 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Interactions among some carriers can alter the overall traffic flow of the drug, favoring intracellular accumulation and toxicity [22]. The use of TDF has been associated with an increased risk for the development of acute or chronic kidney injury and also with different forms of renal toxicity in HIV patients [23][24][25]. From HIV patient data, some reports have associated renal toxicity with a range of variables such as the duration of drug exposure, drug combinations, age, ethnicity, and body mass [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions among some carriers can alter the overall traffic flow of the drug, favoring intracellular accumulation and toxicity [22]. The use of TDF has been associated with an increased risk for the development of acute or chronic kidney injury and also with different forms of renal toxicity in HIV patients [23][24][25]. From HIV patient data, some reports have associated renal toxicity with a range of variables such as the duration of drug exposure, drug combinations, age, ethnicity, and body mass [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fafin et al investigated the association between the duration of treatment with certain antiretroviral drugs (TDF, atazanavir and indinavir) and the evolution of eGFR in HIV-infected patients. Among a cohort of 1750 patients, the average time to chronic kidney disease was 44 months, linking increased TDF treatment duration and dose with a reduction in eGFR [41]. In addition, another trial, in which baseline SCr levels were measured at one, three and 12 months after treatment initiation, a dose-time dependent association between treatment with TDF and a decrease in eGFR was suggested [42].…”
Section: Discussionmentioning
confidence: 99%
“…Tenofovir is primarily eliminated via the kidney by a combination of glomerular filtration and active tubular secretion [4]. Systematic reviews and meta-analyses of randomized controlled trials have indicated an association between TDF-based regimens and an increased risk of renal impairment and bone demineralization [5,6,7], with longer-term studies suggesting that this risk is further increased with cumulative exposure to tenofovir [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%